2022
DOI: 10.1093/jxb/erac197
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and vacuolar localization of fructan exohydrolase derived from onion (Allium cepa)

Abstract: Fructans such as inulin and levan accumulate in certain taxonomic groups of plants and are a reserve carbohydrate alternative to starch. Onion (Allium cepa L.) is a typical plant species that accumulates fructans, and it synthesizes inulin-type and inulin-neoseries-type fructans in bulb. Although genes for fructan biosynthesis in onion were identified so far, no genes for fructan degradation had been found. In this study, phylogenetic analysis predicted that we isolated a putative vacuolar invertase gene (AcpV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This could be due to differences in the kinetics of protein synthesis and/or to post‐translational regulation. Indeed, FEH proteins are close to invertases (Lammens et al, 2009; Oku et al, 2022), which are known to be regulated by protein inhibitors (Hothorn et al, 2010). In addition, the decoupling between transcript levels and activities could be due to partial protein extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to differences in the kinetics of protein synthesis and/or to post‐translational regulation. Indeed, FEH proteins are close to invertases (Lammens et al, 2009; Oku et al, 2022), which are known to be regulated by protein inhibitors (Hothorn et al, 2010). In addition, the decoupling between transcript levels and activities could be due to partial protein extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Plant FEHs are mainly found in the vacuole (Frehner et al, 1984; Oku et al, 2022), where they are involved in the degradation of fructans during periods of reserve mobilization (Morvan‐Bertrand et al, 2001), in fructan trimming during fructan biosynthesis (Lothier et al, 2007; Van den Ende, Clerens, et al, 2003) and in stress tolerance (Yoshida, 2021). Under stress, FEH activity was also detected in the apoplast together with fructans in response to cold in oat ( Avena sativa ; Livingston & Henson, 1998) and wheat ( Triticum aestivum ; Van den Ende et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Also, during the last stages of onion bulb development, 1-FEH activities remained significantly higher in this variety, suggesting that a continuous trimming by 1-FEH inhibits overall FOS accumulation. Therefore, it was decided to search for the 1-FEH gene and purify the native 1-FEH enzyme from developing onion bulbs ( Oku et al , 2022 ).…”
Section: Onion: Economic Importance and Physiological Contextmentioning
confidence: 99%
“…However, it was found that FEHs resembled cell wall invertases instead. Oku et al (2022 ) have now characterized a novel fructan 1-exohydrolase (1-FEH) from onion, an economically important species. This enzyme fits well within the vacuolar invertase subgroup, demonstrating that plant FEHs may be recruited from different types of ancestral invertases.…”
mentioning
confidence: 99%
See 1 more Smart Citation